'No Matter How Harsh, We Are Alive': Coping Strategies of Rural–Urban Migrant Homeless Older People in Ethiopia. (20th May 2022) - Gebeyaw, Getachew; Kotecho, Messay Gebremariam; Adamek, Margaret E.
Abstract: The prevalence of homelessness among older adults in Ethiopia is growing. While prior studies examined the push factors and challenges of homeless elders, little is known about how older people cope with homelessness in a context of limited ageing services. This study explored the coping strategies of homeless older people in Kobo Town, Ethiopia. Purposive sampling was used to identify 10 homeless older people and four key informants. Thematic analysis was used to analyse the data collected through in‐depth interviews. To cope with the challenges faced on the street, homeless older people used various strategies including begging, holy water, drying leftover food, using river water for hygiene and sanitation, sleeping in church compounds, and creating their own social networks. Despite their best efforts, elders' coping strategies could not overcome the barriers imposed by their resource‐poor environment. The findings call attention to the urgent need for a national response to elders' unmet needs including an income support programme and multifaceted support services for older adults in Ethiopia.